Risk Assessment With Value Added Pythagorean Fuzzy Failure Mode and Effect Analysis for Stakeholders - García Aguirre, Pedro Ángel; Pérez Domínguez, Luis; Luviano Cruz, David; Martinez Gomez, Erwin Adan; Perez Olguin, Ivan Juan Carlos; Davalos Ramirez, Jose Omar (2021)
The new product development process (NPDP) is crucial for maintaining business up and running in manufacturing corporations worldwide. NPDP helps firms improve their profits, where stakeholder attention is mostly focused. NPDP Risk Assessment (NPDP-RA) is a vital activity to achieve a successful new product launch. However, managing different kinds of risks over the process presents enormous challenges; thus, risk assessment over NPDP still shows gaps, even when different tools are employed to identify, mitigate, and eliminate risks throughout the process. The identified gaps are mainly produced because the uncertainty added by the individuals assessing the risks, and the currently used tools are generally focused on a single phase of the NPDP, disregarding the stakeholders’ project objectives. This paper presents the main NPDP risks for stakeholders through the NPDP phases; likewise, the integration of Pythagorean fuzzy dimensional analysis – failure mode and effect analysis and value stream mapping (PFDA-FMEA-VSM). This novel integrated method is intended to improve the manner to perform the NPDP-RA for stakeholders. A practical example is presented to demonstrate the proposed integration of PFDA-FMEA-VSM for stakeholders at NPDP of electronic devices project.